Pengaruh Aset Pajak Tangguhan, Beban Pajak Tangguhan dan Ukuran Perusahaan terhadap Manajemen Laba - Alimah Tamira; Dirvi Surya Abbas; Budi Rohmansyah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2020 period with a total sample of 49 companies. The sampling technique uses purposive sampling technique. The analytical method used is panel data regression analysis. This test uses quantitative research methods. The research results show that deferred tax assets, deferred tax expenses and company size have no effect on earnings management.